al- Nejd, a fortified Samad late Iron Age settlement in Sharqiyya North Governorate, Sultanate of Oman: an attempted reconstruction - Yule, Paul; Ayash, Nasser Bovoleti (Athīrat, 2025)
Abstract First reported in 2014, a fortified site atop a small mountain adjacent to the village of al-Nejd shows another facet of the settlements of the little-known Samad Late Iron Age (SLIA). Until recently, few settlements of the Early Iron Age and late pre-Islamic period are recorded and published in the land between the Oman Peninsula (U.A.E.) and Oman’s southern province, Dhofar. While analyzing graves with skeletons and finds of the latter period yields information about their owners, settlements lag far behind. With this background, al-Nejd offers new insight into the settlement, in addition to the first coin to be found in Oman. The authors attempt graphic documentation to contextualize the architecture and answer two questions. First, is there a typical kind of SLIA fortification separate from other periods? Second, how closely is the SLIA related to its neighbors and the preceding period in terms of material culture and architecture?